2022
DOI: 10.2478/cejpp-2022-0004
|View full text |Cite
|
Sign up to set email alerts
|

No escape from COVID-19 consequences: cross-sectoral evaluation of impact on unemployment in Slovakia

Abstract: The coronavirus disease 2019 (COVID-19) pandemic, which hit the world in 2020 and is still persisting, has significantly impacted many areas of people's lives. The shutdown anti-pandemic measures implemented by the governments also caused the development of unemployment worldwide. In Slovakia, the restrictions or even complete closure of the operation and activities of the companies caused rising unemployment in some sectors, while in some sectors, the impact was not so substantial. Therefore, the main aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…From the global point of view of the evaluation of the results, even in the case of the Slovak economy, it has been confirmed that the applied antipandemic measures did not have the same impact on all economic sectors. In a study by (Svabova et al, 2022) the authors also focused on the analysis of the pandemic impact on unemployment in individual sectors. This study focused on the period up to April 2021 and identified the most affected sectors as F -construction (on average almost 89% increase in unemployment compared to the prediction), I -accommodation and food service activities (on average 88% increase in unemployment) and R -arts, entertainment and recreation (on average 65% increase).…”
Section: Discussionmentioning
confidence: 99%
“…From the global point of view of the evaluation of the results, even in the case of the Slovak economy, it has been confirmed that the applied antipandemic measures did not have the same impact on all economic sectors. In a study by (Svabova et al, 2022) the authors also focused on the analysis of the pandemic impact on unemployment in individual sectors. This study focused on the period up to April 2021 and identified the most affected sectors as F -construction (on average almost 89% increase in unemployment compared to the prediction), I -accommodation and food service activities (on average 88% increase in unemployment) and R -arts, entertainment and recreation (on average 65% increase).…”
Section: Discussionmentioning
confidence: 99%